Cerebral Mass Lesion in Medulla Oblongata Causing Intractable Hiccups. Issue 3 (August 2015) - Nemoto, Masaaki; Miyazaki, Chikao; Harada, Naoyuki; Kondo, Kosuke; Nomoto, Jun; Masuda, Hiroyuki; Sugo, Nobuo; Kuroki, Takao
<x xml:space="preserve">Abstract</x> Intractable hiccups caused by an intracranial mass lesion are rare. We encountered surgical cases of cavernous angioma and hemangioblastoma in the medulla oblongata, which manifested with intractable hiccups. Herein, we report on 2 cases: case 1, a 30-year-old woman with a past medical history of surgery for cerebellar hemangioblastoma. The disease manifested with intractable hiccups, and a mass lesion was observed in the medulla oblongata on magnetic resonance imaging (MRI). During surgery, a vascular-rich tumor was localized near the obex of the mid-dorsal portion of the medulla oblongata. The hiccups were resolved immediately after total tumor excision, no event occurred thereafter, and the patient was discharged. The pathologic diagnosis was hemangioblastoma. Case 2, in a 22-year-old man, a lesion was observed in the dorsal portion of the medulla oblongata on computed tomography and MRI was performed to investigate the cause of intractable hiccups. During surgery, a mass lesion was present in the right dorsolateral aspect of the medulla oblongata. The hiccups resolved immediately after total excision of the lesion. No neurological deficit occurred, and the patient was discharged. The lesion was pathologically diagnosed as a cavernous angioma. In conclusion, a search for a dorsal medullary lesion using MRI is necessary when investigating intractable hiccups. To resolve intractable hiccups, the active application of surgical excision of the mass lesion is recommended.